The Iron Biology Status of Peritoneal Dialysis Patients May be a Risk Factor for Development of Infectious Peritonitis. Issue 4 (July 2019) - Aldriwesh, Marwh; Al-Dayan, Noura; Barratt, Jonathan; Freestone, Primrose
Background: Infectious peritonitis is a clinically important condition contributing to the significant mortality and morbidity rates observed in peritoneal dialysis (PD) patients. Although some of the socioeconomic risk factors for PD-associated peritonitis have been identified, it is still unclear why certain patients are more susceptible than others to infection. Methods: We examined the molecular components of human peritoneal dialysate (HPD) in an attempt to identify factors that might increase patient susceptibility to infection. Characterization studies were performed on initial and follow-up dialysate samples collected from 9 renal failure patients on PD. Results: Our in vitro data showed that peritonitis-causing bacteria grew differently in the patient dialysates. Proteomic analysis identified an association between transferrin presence and infection risk, as peritoneal transferrin was discovered to be iron-saturated, which was in marked contrast to transferrin in blood. Further, use of radioactive iron-labeled transferrin showed peritoneal transferrin could act as a direct iron source for the growth of peritonitis-causing bacteria. We also found catecholamine stress hormones noradrenaline and adrenaline were present in the dialysates and were apparently involved in enhancing the growth of the bacteria via transferrin iron provision. This suggests the iron biology status of the PD patient may be a risk factor for development of infectious peritonitis Conclusions: Collectively, our study suggests transferrin and catecholamines within peritoneal dialysate may be indicators of the potential for bacterial growth in HPD and, as infection risk factors, represent possible future targets for therapeutic manipulation.